The results of a pedagogical experiment aimed at improving overall endurance in football during the training period - Lyubetsky N.P. ,; Agafonov S.V. ,; Fomenko V.D. ,; Chub S.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to improve the methodology for developing the general endurance of football players using high-intensity interval training. Methods and structure of the study. The experimental study was carried out on the basis of the State Budgetary Institution of Additional Education "Sports School of Olympic Reserve No. 19 named after B. Kabargin" in the conditions of the training process. Direct participants of the pedagogical experiment were 20 young football players aged 13-14 years at the training stage of preparation in the sports school, 10 of whom were included in the experimental group and 10 players in the control group. Complexes of high-intensity interval training were developed, aimed at increasing the aerobic performance of the athletes' body and in their content represented high-intensity exercises that alternated with various variations of rest. Results and conclusions. It was established that the use of the proposed sets of exercises in the training sessions of football players led to positive changes in a number of endurance indicators in the experimental group. The positive dynamics of the parameters of general endurance was especially clearly observed in specific tests for football players of this age period.